2021
DOI: 10.1590/0366-69132021673843182
|View full text |Cite
|
Sign up to set email alerts
|

Efeito do ácido esteárico em scaffolds de alumina obtidos por manufatura aditiva usando o método de fabricação por filamento fundido

Abstract: Resumo As cerâmicas porosas podem ser utilizadas nas mais diversas aplicações, como na indústria petroquímica e na área da saúde. No entanto, é difícil produzir cerâmicas com formas complexas usando processos convencionais. Neste trabalho, diferentes termoplásticos (PEBD, ABS e PLA) foram utilizados para a extrusão de filamentos com alumina submicrométrica. Estes filamentos foram extrudados com e sem ácido esteárico que, posteriormente, foram utilizados na manufatura aditiva para a impressão de estruturas poro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The apparent viscosity behavior of the mixtures showed a reduction in viscosity compared to pure ABS concerning shear rate (as shown in Figure 4), similar to the findings of Calafel et al 45 and Smirnov et al 46 This indicates that the mixtures exhibit viscoelastic fluid properties and can be extruded through a finer nozzle under appropriate printing pressure without clogging, meeting the requirements of 3D printing. 47 One contributing factor is the presence of stearic acid or carnauba wax (acting as a surfactant/dispersant), as mentioned by Hnatkova et al 48 and Gorjan et al, 49 and demonstrated in the work of Faccio et al, 26 in which the presence of stearic acid decreased the viscosity, increasing the fluidity of mixtures of ABS with alumina. The percentage increase of surfactant/dispersant from 15 to 25% on the amount of filler in the composites with basic bismuth carbonate was necessary to aid the production of a filament with adequate cylindrical geometry since the increase in the percentage of stearic acid and carnauba wax helps to reduce viscosity.…”
Section: Rheologymentioning
confidence: 94%
See 2 more Smart Citations
“…The apparent viscosity behavior of the mixtures showed a reduction in viscosity compared to pure ABS concerning shear rate (as shown in Figure 4), similar to the findings of Calafel et al 45 and Smirnov et al 46 This indicates that the mixtures exhibit viscoelastic fluid properties and can be extruded through a finer nozzle under appropriate printing pressure without clogging, meeting the requirements of 3D printing. 47 One contributing factor is the presence of stearic acid or carnauba wax (acting as a surfactant/dispersant), as mentioned by Hnatkova et al 48 and Gorjan et al, 49 and demonstrated in the work of Faccio et al, 26 in which the presence of stearic acid decreased the viscosity, increasing the fluidity of mixtures of ABS with alumina. The percentage increase of surfactant/dispersant from 15 to 25% on the amount of filler in the composites with basic bismuth carbonate was necessary to aid the production of a filament with adequate cylindrical geometry since the increase in the percentage of stearic acid and carnauba wax helps to reduce viscosity.…”
Section: Rheologymentioning
confidence: 94%
“…An important factor for 3D printing processing is related to the mixture's viscosity, which decreases as the amount of filler in the mix increases 24 . Furthermore, the addition of waxes and carboxylic acids (with the function of surfactants) helps in solving problems of dispersion and agglomeration of the added charge 24–26 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation